2011
DOI: 10.1136/vr.c5430
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of equine sarcoids by topical aciclovir application

Abstract: Based on the anecdotally reported eradication of a sarcoid using aciclovir cream, the curative potential of this ointment was investigated in 22 sarcoid-affected horses referred to the Equine Clinic Tillysburg, Austria, between 2006 and 2009. Sarcoid disease was diagnosed by clinical examination and bovine papillomavirus types 1 and 2 from intact skin and tumour tissue. As nine horses had more than one lesion, a total of 47 sarcoids were treated by daily topical application of aciclovir 5 per cent cream for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 12 publications
0
18
1
10
Order By: Relevance
“…O uso tópico de aciclovir tem sido um tratamento promissor, pois apresenta bons resultados, é de fácil utilização e tem baixo custo quando comparado a outras terapias, como a BCG (Knottenbelt et al, 1995, Bromerschenkel & Figueiró, 2013. Stadler et al (2011) utilizaram o creme de aciclovir a 5% em 47 lesões de sarcóide equino, diariamente durante dois a seis meses. Ao término do experimento, todos os 47 tumores responderam satisfatoriamente ao tratamento, sendo que a regressão completa ocorreu em 68% (32/47) das lesões.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O uso tópico de aciclovir tem sido um tratamento promissor, pois apresenta bons resultados, é de fácil utilização e tem baixo custo quando comparado a outras terapias, como a BCG (Knottenbelt et al, 1995, Bromerschenkel & Figueiró, 2013. Stadler et al (2011) utilizaram o creme de aciclovir a 5% em 47 lesões de sarcóide equino, diariamente durante dois a seis meses. Ao término do experimento, todos os 47 tumores responderam satisfatoriamente ao tratamento, sendo que a regressão completa ocorreu em 68% (32/47) das lesões.…”
Section: Discussionunclassified
“…A falha no tratamento com aciclovir pode estar proporcionalmente associada à espessura da lesão, sugerindo que a droga possui habilidade moderada para penetrar em áreas mais profundas. Portanto, recomenda-se a exérese de massas tumorais maiores que 5 mm de diâmetro com posterior utilização do creme de aciclovir a 5% sobre a lesão (Stadler et al, 2011, Taylor & Haldorson, 2013, conforme feito no segundo protocolo terapêutico estabelecido no presente relato.…”
Section: Discussionunclassified
“…Entre as terapias incluem-se negligência benigna, ligadura, remoção cirúrgica completa, crioterapia, hipertermia por radiofrequência, injeção intralesional com cisplatina, uso de 5-fluorouracil, laser com dióxido de carbono, radioterapia, administração de AW4-LUDES, imunomodulação com BCG, imiquimode, vacinas autólogas e aciclovir (KNOT-TENBELT et al, 2008;STADLER et al, 2011;CESCON, 2012;BERGVALL, 2013;BROMERSCHENKEL et al, 2013).…”
Section: Tratamentounclassified
“…Topical treatment with acyclovir has been described to result in complete regression in 68% of occult, verrucous, nodular or mixed equine sarcoids [5]. In addition, a recent ex vivo study has shown that acyclovir concentrations reached in the dermal layers after topical administration on sarcoid-affected equine skin are high enough to possibly achieve an antiviral effect [6].…”
Section: Introductionmentioning
confidence: 99%